Harvest Payment System in Workers' Wages: an Islamic Economic Perspective - Eny Latifah; Hannik Lailatul Fitroh (MultiTech Publisher, 2023)
This research aims to show how to maintain the existence of the Sharia accountant profession in the era of the Industrial Revolution 5.0 .The research method is qualitative with the type of literature study. The result of the research is that the existence of the Islamic accountant profession in the era of the industrial revolution 5.0 in Indonesia will still be maintained in various ways, namely: (1) Designing assignments that are not routine and not structured, where the performance of judgment and wisdom really requires human mindset and special skills that can only be done by humans and cannot be done by technology such as robots or other technological tools; (2) Using Technical Skill and Ethics (TEQ) by understanding relevant technology and playing a role with ethics and a sense of responsibility not only to stakeholders in the world but to Allah SWT in the afterlife; (3) The task of Islamic accountants as supervisors of sharia-based industries provides a great opportunity for Islamic accountants to maintain their existence with the development of Islamic entities on sharia principles and rules in the digital era; (4).There is no need to worry about the upcoming threats to the 5.0 industrial revolution in the Islamic accounting profession because technological developments cannot be prevented. However, what must be done is to adapt and learn and improve the quality of accounting education by providing services both virtual and conventional in order to create the quality of students who are competent in the field of accounting; and (5) Technology will forever be unable to replace the role of ethics and Islamic religious values and principles in the concept of business or transactions based on Islamic sharia.